Robot Beroda Pendeteksi Dan Pencatat Kebocoran Pipa Gas - Hadi, Ahmad Nur; , Heru Supriyono, ST. MSc. PhD (2017)
In the industrial world, a gas leak can cause a loss and can inhibit the gas distribution company. In addition, it can also threaten human life if the leaking gas is toxic and flammable gas. This time to check the gas pipeline leaks is done manually by humans. To overcome this problem researchers have an idea of research that aims to replace human tasks in checking a gas leak with a wheeled robot. In this study, the robot has been designed with arduino nano as a controller and two motors as their driving force and a motor driver L298N as motor controllers. Wheeled robot is equipped with a gas sensor MQ-2 is used to detect a gas leak and the line sensor TCRT5000 used to follow a predetermined path in the form of black lines. At wheeled robot is also equipped with a DS3231 RTC timer and microSD which is used to record the results and there is a LCD to display the results of sensor readings. At wheeled robot is also equipped with a buzzer and LED lights are used for warning signals in case of leakage. The system is the work of a wheeled robot that the robot will be activated by a predetermined time and the robot will follow the black line running along the gas pipeline. If the MQ-2 gas sensor detects gas leaks in the pipe, then the robot will stop and it will give a warning LED flame that flickers and the sound of the buzzer. In the event of a leak that the robot will record the results of the gas sensor into the microSD and will display it to the LCD. The results obtained from this study is that the robot can work according to a predetermined schedule. Robot goes according to existing lines as well as its detection is working properly. Robot detect leaks if the leak rate of less than 6 and the robot will stop and give a warning buzzer and LED Flash. Then the robot will show the result to the LCD and will record the results to a microSD card with the ".txt" format. Keywords: arduino, gas sensor mq2, line sensor, microsd, rtc ds2321, wheeled robots.